The impact of policy measures on trade in services in Latin America and the Caribbean - Danielle Trachtenberg (Inter-American Development Bank (IDB), 2021)
This paper uses data on policy measures affecting services operation and trade to document and estimate the impact of different types of policy measures on services exports and imports, with a focus on Latin America and the Caribbean. It finds that market-entry measures are important to both total services exports and imports in the region and bilateral trade flows with the United States, while measures relating to the operation of service providers are important for bilateral trade flows with the United States.
Keywords: F13; F14; F15; 330; International trade; trade in services; trade policy; regulation